Determination of sulfate in ethanol fuel using an electrode chemically modified with polypyrrole by flow injection analysis - Castilho, Michelle de Souza [UNESP]; Yamanaka, Hideko [UNESP]; Oliveira, Marcelo Firmino de; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Diva Enterprises, 2010)
In this work, an electrode chemically modified with polypyrrole (PCME) was employed for determination of sulfate in ethanol fuel using a FIA system. The PCME was prepared by polymerization of pyrrole at a glassy carbon electrode by means of cyclic voltammetry technique. An analytical curve from 1.0 x 10−5 to 8.0 x 10−5 mol L−1 was obtained in flow injection system based on the PCME. An amperometric sensibility of 2.3 x 10−3 A mol−1 L and a detection limit of 2.5 x 10−6 mol L−1 were achieved. The proposed method was employed for determination of sulfate ions in commercial samples of ethanol fuel. The results were in good agreement with those obtained by the ionic chromatographic method.
Keywords: Ethanol fuel; Sulfate determination; Polypyrrole-film; Flow injection analysis